2006
DOI: 10.1158/1535-7163.mct-05-0376
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the mechanism by which selenium deactivates Akt in prostate cancer cells

Abstract: The up-regulation of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway is prevalent in many cancers. This phenomenon makes PI3K and Akt fruitful targets for cancer therapy and/or prevention because they are mediators of cell survival signaling. Although the suppression of phospho-Akt by selenium has been reported previously, little information is available on whether selenium modulates primarily the PI3K-phosphoinositidedependent kinase 1 (PDK1) side of Akt phosphorylation or the phosphatase side of Akt dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 38 publications
2
37
1
Order By: Relevance
“…It has been well known that PI3K triggers cytoprotective events in response to diverse stimuli (31)(32)(33). Interestingly, however, in this study we found that PI3K is critically required for the radiation-induced apoptotic cell death.…”
Section: Discussioncontrasting
confidence: 61%
“…It has been well known that PI3K triggers cytoprotective events in response to diverse stimuli (31)(32)(33). Interestingly, however, in this study we found that PI3K is critically required for the radiation-induced apoptotic cell death.…”
Section: Discussioncontrasting
confidence: 61%
“…For example, the protein phosphatase PP2B, also called calcineurin, is regulated by Ca 2ϩ , and it is able to dephosphorylate Akt (Rusnak and Mertz, 2000;Wu et al, 2006). Increases in intracellular Ca 2ϩ levels result in PP2B association with calmodulin and subsequent activation of PP2B phosphatase activity (Rusnak and Mertz, 2000).…”
Section: Protein Phosphatases Facilitate Hlya-mediated Akt Dephosphormentioning
confidence: 99%
“…3). A few examples include curcumin (68), selenium (69), and the flavonoids quercetin (70), genistein (71), apigenin (72), and silibinin (73). Most of these effects Targeting the AKT Protein Kinase for Chemoprevention have been shown in vitro, in some cases using doses far above those that are physiologically achievable.…”
Section: Modulating Akt Signaling To Prevent Cancermentioning
confidence: 99%